Effect of crystallization parameters and presence of aqueous extract of Nigella Sativa on growth inhibition of calcium oxalate monohydrate particles. (17th February 2018) - Abdel-Aal, E. A.; Yassin, A. M. K.; El-Shahat, M. F.
ABSTRACT: For the first time, nucleation kinetics, crystal growth and agglomeration of calcium oxalate monohydrate (COM) are studied as a crystal growth inhibitor with and without Nigella Sativa (NS) extract. The induction period was determined under different supersaturation ratios ranging from 1.63 to 4.51 at 37°C using the conductivity method. Based on the classical homogeneous nucleation theory; the critical nucleation parameters were evaluated at higher supersaturation ratio. The calculated surface energy was increased from 7.97 mJ/m 2 without additive to 10.31 mJ/m 2 with NS extract. However, the nucleation rate at a supersaturation ratio of 3.26 corresponding to 5.44 with the NS extract was decreased from 3.9 × 10 29 nuclei/cm 3 .s (without additive) to 1.3 × 10 29 nuclei/cm 3 .s with NS extract addition. The number of molecules required for the formation of a stable nucleus was calculated with and without NS extract at different supersaturation ratios. The crystallite sizes of the formed crystals without and with the additive are 93 and 51 nm, respectively. Scanning electron microscopy (SEM) photomicrographs show the formation of small crystals and less aggregated with the NS inhibitor compared with the baseline (without the inhibitor). This study can help us with a clear understanding of the inhibition mechanism of an aqueous NS extract on COM crystals.